What Motivates Talented Medical Students to Study Simultaneously at Master of Public Health (MPH)? - Sahar Manavi; Saharnaz Nedjat; Parvin Pasalar; Reza Majdzadeh (Tehran University of Medical Sciences, 2013)
Nearly three decades ago, the Master of Public Health (MPH) academic degree was introduced to Tehran University of Medical Sciences' School of Public Health, Tehran, Iran. A new program for simultaneous education of medical, pharmaceutical and dental students was initiated in 2006. Talented students had the opportunity to study MPH simultaneously. There were some concerns about this kind of admission; as to whether these students who were not familiar with the health system had the appropriate attitude and background for this field of education. And with the present rate of brain drain, is this just a step towards their immigration without the fulfillment of public health?This qualitative study was conducted in 2012 where 26 students took part in focused group discussions and individual interviews. The students were questioned about their motivation and the program's impact on their future career. The participants' statements were analyzed using thematic analysis.THE PRIMARY MOTIVATIONS OF STUDENTS WHO ENTERED THIS PROGRAM WERE: learning health knowledge related issues, gaining a perspective beyond clinical practice, obtaining a degree to strengthen their academic résumé, immigration, learning academic research methods and preparing for the management of health systems in the future.Apparently, there was no considerable difference between the motivation of students and the program planners. The students' main motivation for studying MPH was a combination of various interests in research and health sciences issues. Therefore, considering the potential of this group of students, effective academic investment on MPH can have positive impact.